Appearance of recurrent dermatofibrosarcoma protuberans in postoperative MRI follow-up. Issue 11 (November 2020) - Sedaghat, Sam; Schmitz, Frederick; Sedaghat, Maya; Nicolas, Volkmar
Abstract: Purpose: To analyze the appearance of recurrent dermatofibrosarcoma protuberans (DFSP) in postoperative MRI follow-up and to assess the occurrence of postoperative soft tissue changes detected in MRI. Methods: A total of 464 MRI follow-up scans of 32 patients with histologically proven diagnosis of DFSP were analyzed. MR imaging was performed using a 1.5T MRI system. Recurrent DFSP was examined for signal intensity, contrast behavior, appearance, and extent in MRI. Results: The mean age of the patients was 44, 5±17, 1 years. Recurrences of DFSP occurred 26±23.3 months after primary tumor resection in the mean (Min.: 9, Max.: 60). In 25% of the patients ( n = 8), recurrences of DFSP were detected. Recurrent DFSP most often showed a nodular and homogeneous configuration with well-defined borders and marked contrast enhancement, and a hyperintense signal in PD-weighted and turbo inversion recovery magnitude sequences. All recurrences were well detected in the follow-up MRIs regardless of the performed plastic surgery procedure. Lateral and depth margins had no significant impact on the local recurrence rate. In all, 88% of the patients developed subcutaneous tissue edema ( p < 0.01), followed by muscle edema (34%, p = 0.02), and postoperative seroma (22%). Conclusion: Recurrent DFSP mainly appear uniform and clearly delimitable on MRI as nodular, homogeneous, and well-defined lesions with marked contrast enhancement. Therefore, MRI is a valuable tool for postsurgical follow-up. Nearly all patients develop subcutaneous edema after the resection of DFSP.